The a to Z of British Radio - Street, Seán (Rowman & Littlefield Publishers, 2009)
Founded in 1922, the British Broadcasting Corporation is probably the most well-known national radio corporation in the world, but the BBC is just part of the British radio picture. There are 'pirate' radio stations, community radio, commercial radio, and more recently, experimentation and development in the digital arena. All aspects of the 85 years of UK radio, from issues of regulation to the role played by commercial operators prior to World War II, are covered in this new book by SeOn Street. The A to Z of British Radio relates the history of this medium through a chronology, an introductory essay, a bibliography, and several hundred cross-referenced dictionary entries on the BBC and other companies, many of the specific stations, the more memorable programs and those who wrote for or appeared on them, and the administrative and technical aspects. This quick reference tool's structure and ease of navigation will have scholars, students, radio industry professionals, journalists, and critics turning to it again and again.